Fast cities - Andersen, Morten 1965-; Flemming, Gösta 1955- (Journal, 2018)
More and more of us live in cities, more than half of us actually and that figure is just growing, rapidly. But it's not in Europe or North America we live. Well some of us do. The largest and fastest growing cities we find in Asia, South America and Africa. But bigger doesn't necessarily mean better and the challenges with pollution, overpopulation, poverty, housing, transportation, drinking water, sanitation, energy, crime, social inequality and so on seems endless. Endless cities in every sense. With curiosity, camera and boots made for walking I set out to explore the streets of Mexico City, Cairo, Mumbai, Kolkata, Dhaka, Shanghai, Sao Paulo, Djakarta and Lagos. All megacities with a population of 10 or more millions, sometimes up to 20 with the greater metropolitan areas included. Cities with two, three, four times as many people than in little Norway where I live. Except from Shanghai they were all new ground to me, not that I recognized anything from my late 1980s visit there, things change fast and with just about a week in each place, accompanied with my usual jetlag and diarrhea, I am just scratching on a tiny bit of the surface here. Usually when we see photographic work from the megacity it's often about spectacular architecture so I have focused more on the human element and the energy of the city experienced at a grass-root level. How people move, look, play, dance - small stories, from big cities.